Not by bread alone... forests and rural livelihoods in Sub-Saharan Africa - Kaimowitz, David (European Forest Institute, 2003)
Tens of millions of rural households in Sub-Saharan Africa rely heavily on forest products for subsistence and to supplement their cash incomes. The poorest households, women and children generally rely on them most. Forests are indirectly linked to rural livelihoods through their role in governance, the macroeconomy and climate change. Failure to develop legitimate government structures and invest in social services in forested region has contributed to violent conflict, illegal activities and weakening of the rule of law. That discourages investment and lowers economic growth. In certain Central and West African nations, commercial forestry provides a large share of the foreign exchange. From the environmental point of view, forests serve as carbon sinks, slowing down global warming and reducing its negative effects on small-scale agriculture.This paper first discusses the contribution of forest resources to rural livelihoods and then examines some related threats and opportunities. Finally it makes policy recommendations.